Manajemen Informasi Publik BPS dalam Menghadapi Penolakan Masyarakat pada Sensus Ekonomi 2026 - Khoifaturrahman Khoifaturrahman; Berlian Berlian; Ulfatur Rizkiyah; Ulil Himamil Aliyah; Imraatus Shalihah; Yeni Tri Nur Rahmawati (Jurnal Manajemen dan Ilmu Administrasi, 2026)
The implementation of the 2026 Economic Census (SE2026) by Statistics Indonesia (Badan Pusat Statistik/BPS) has encountered significant challenges due to resistance from a number of respondents, particularly Micro, Small, and Medium Enterprises (MSMEs). This resistance is primarily driven by concerns over the potential misuse of collected data for taxation purposes, as well as issues related to data privacy. This study aims to analyze the public information management strategies employed by Statistics Indonesia (BPS) to mitigate such resistance. Using a descriptive qualitative approach through a literature review and media content analysis, the findings reveal that BPS has addressed public resistance through three main strategies: (1) implementing large-scale information clarification (counter-narrative) to emphasize the independence of census data from the taxation system; (2) strengthening public education regarding legal guarantees of data confidentiality as stipulated in Law No. 16 of 1997 concerning Statistics; and (3) enhancing cross-sector public communication through collaboration with the Regional Communication and Informatics Offices (Diskominfo) and other relevant government agencies. The study concludes that transparent public communication and clear legal assurances regarding data confidentiality are key factors in restoring public trust and ensuring the successful implementation of the national economic census.